Effects of action observation therapy with Otago exercises on balance and quality of life in older adults - Shah Ahmed; Farah Manzoor; Hafsa Naseem; Amna Qandil Ansari (The Rehabilitation Journal, 2024)
Background: Balance problems and falls are prevalent issues, especially among older adults. Otago exercise is one of the interventions applied to the geriatric population to prevent falls and balance problems, The Action observation therapy with the Otago exercise program can be a more beneficial intervention method to decrease the prevalence of falls and balance issues among older people.